Computer Aided Detection of Diabetes Retinopathy and Analysis through ANFIS and Optimtool (International Journal of Engineering and Computer Science, 2015)
The entire human body can be controlled using a Computer aided diagnosis (CAD). One of such technology is CAD system for diabetic retinopathy detection. Damage or degeneration of the optic nerve, the brain or any part of the visual pathway between them, can impair vision. Diabetic Retinopathy (DR) does not exhibit any distinctive symptoms which the patient cannot easily perceive until a severe stage is reached. This is because lack of specialized ophthalmologists i.e., 1:1000 ratio availability of doctors to patients together with associated higher medical costs makes regular check up costly. We proposed to develop a low cost and versatile Computer Aided Diagnosis (CAD) systems. It can be achieved by Adaptive Neuro Fuzzy Inference System (ANFIS) assisted Diagnosis and by genetic algorithm through Fundus Image. So that we can estimate the damage of retina and the appropriate treatment to the patient can be recommended to save them from vision loss.